Avaliação do uso de macrófitas aquáticas flutuantes para tratamento de efluentes da aquicultura - Vasconcelos, Vera Mônica de (Universidade Federal Rural do Semi-Árido, 2018)
Aquaculture is an important economic activity with positive social impact, since it generates food, employment and income, however, negatively impacts the environment, mainly by the production of effluent rich in sedimentary solids, organic matter, phosphorus and nitrogen, being the last two, responsible for eutrophication of water courses, causing change in aquatic biota. In this sense, it was intended to evaluate the efficiency of floating aquatic macrophytes in the treatment of effluents from aquaculture. The experiment was conducted in fully randomized experimental design, with 7 treatments and 3 repetitions, the treatments were composed by control/witness, Eichhornia crassipes, Pistia stratiotes, Salvinia molesta, Eichhornia crassipes and Pistia stratiotes, Eichhornia crassipes and Salvinia molesta and Pistia stratiotes and Salvinia molesta, being determined in each treatment, before and after the experiment, temperature, PH, turbidity, dissolved oxygen, electrical conductivity, total nitrogen, N-nitrite, N-nitrate, N-ammoniacal, total phosphorus, total alkalinity, BOD and COD. Significant interaction was found for PH, dissolved oxygen, total nitrogen, N-nitrite and N-nitrate as a function of time.. None of the treatments were efficient for phosphorus removal and the treatment with Pistia stratiotes was efficient in reducing total nitrogen
Keywords: Agronegócio; Impactos ambientais; Recursos naturais; Sustentabilidade; Agribusiness; Environmental impacts; Natural resources; Sustainability; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE